Solubility of triclabendazole as a factor determining the activity of its solid dispersions with polymers - M. S. Khalikov (Российский паразитологический журнал)
The purpose of the research is to study solubility of triclabendazole-based (TCB) solid dispersions (SD) and polymers obtained under optimal conditions of mechanochemical technology; and to confirm chemical stability of a TCB substance by the HPLC method both during its SD preparation and their storage.Materials and methods. The research used a TCB substance, polyvinylpyrrolidone (PVP), arabinogalactan (AG), and licorice extract (LE) that contained 25% glycyrrhizinic acid (GA). For machining, the initial components were taken in a 1 : 9 weight ratio and machined in an LE-101 drum mill on rolls with a drum rotating at a speed of 55–60 rpm with a 1 : 17 process module for 1 to 6 hours with sampling to evaluate the TCB solubility and stability. The TCB sample solubility and its stability were evaluated in these samples by HPLC.Results and discussion. The machining of the TCB substance with selected polymers obtained the corresponding SDs of the following compositions: TCB : PVP (1 : 9), TCB : AG (1 : 9), TCB : PVP : AG (1 : 4.5 : 4.5) and TCB : LE (1 : 9), which were free-flowing powders with enhanced solubility for TCB (up to 34). The evaluation of previously obtained samples of TCB SDs showed that the solubility decreased slightly over time. For example, a decrease in solubility for TCB : AG (1 : 9) was observed from 10 to 8 (the sample after 2 h of machining) and from 23 to 18 (the sample after 4 h of machining). The chemical stability was observed of the TCB substance in its SD samples obtained earlier.